Influence of Rosiglitazone on the Expression of PPARγ, NF-κB, and TNF-α in Rat Model of Ulcerative Colitis - Jing-Wei Mao; Hai-Ying Tang; Ying-De Wang (Gastroenterology Research and Practice)
Aim. To observe the disease activity index (DAI) and the colonic mucosa damage index (CMDI), detect the colonic mucosal expression of PPARγ, NF-κB, and TNF-α in rats with ulcerative colitis (UC), and to investigate the protective role of rosiglitazone in UC. Methods. Sprague-Dawley (SD) rats were divided into three groups: a control group, a rosiglitazone treatment group, and a UC model group. Rats were sacrificed on days 7, 14, 21, or 35 following administration of treatment after enema and DAI, CMDI and colonic expression of PPARγ, NF-κB, and TNF-α were assessed. Results. In the UC model group, DAI, CDMI and the colonic expression of NF-κB and TNF-α increased significantly compared to the control group at all timepoints, but PPARγ decreased significantly. Furthermore, in the rosiglitazone treatment group, DAI and CMDI decreased significantly on the 14-day, 21-day, and 35-day timepoints compared to the UC model group; the colonic expression of NF-κB and TNF-α decreased compared to UC model group at all timepoints, but the PPARγ expression increased significantly. Conclusions. Rosiglitazone can alleviate colonic mucosal inflammation and have the protective role on UC by upregulating PPARγ expression and downregulating NF-κB and TNF-α expression.